Reaching millions: HarvestPlus 2015 annual report - HarvestPlus (International Food Policy Research Institute, 2016)
2015 has been a momentous year for the global biofortification movement. We estimate that 15 million people in eight HarvestPlus target countries are now growing and eating nutrientrich staple foods. Exciting nutrition data demonstrates that biofortified foods can reverse iron deficiency and reduce the incidence and duration of diarrhea, one of the leading causes of preventable death in children under five.